Shared Decision-Making for Advanced Renal Cell Carcinoma: Focus on Adverse Event Management of Axitinib Plus IO: A Vodcast - Edwin M. Posadas; Nancy Moldawer; Greg Biddulph; Dharanija Rao (Oncology and Therapy)
Abstract Shared decision-making is essential to the care of patients with advanced renal carcinoma which can empower patients and help the healthcare team understand the patient’s goals of care. An important topic during the shared-decision making process is identification and management of treatment-related adverse events. A patient author and two healthcare professionals with real-world experience provide insight into the importance of shared decision-making and its utility in the management of treatment-related adverse events in patients with renal cell carcinoma who are receiving axitinib in combination with an immunotherapy agent.